Fabrication and characterization of nanofibrous scaffold developed by electrospinning - Dhandayuthapani,Brahatheeswaran (2011)
Electrospinning has been recognized as an efficient technique for the forming of polymer nanofibers. Silk fibroin (SF) nanofibers were electrospun from SF solution using trifluoroacetic acid solution as a solvent. In the present work, we have systematically evaluated the effects of instrument parameters, including applied voltage, tip-target distance, solution flow rate, solution parameters; such as polymer concentration and solution viscosity on the morphology of electrospun SF fibers. The applied voltage and flow rate was monitored at fixed tip target distance during the electrospinning process and it was correlated with the characteristics of the fibers obtained. The number of deposited fibers also increases with the applied voltage. Also, viscosity, flow rate and applied voltage strongly affect the shape and morphology of the fibers. A particular interest, we demonstrated that by monitoring the applied voltage and flow rate it is possible to control the fibers morphology and bead concentration. Rheological study showed a strong dependence of spinnability and fiber morphology on solution viscosity. Solution concentrations has been found to most strongly affect fiber size, with fiber diameter increasing with increasing solution concentration and the morphology of the deposition on the collector changed from spherical beads to interconnected fibrous networks. FTIR analysis clearly shows that there are no spectral differences between fibers and which suggests that there was no chemical modification developed during the process. Under optimized conditions, homogenous (not interconnected) SF fibers with a mean diameter of 234 nm were prepared.